Calidad de desempeño del comité de gestión pedagógica y su influencia en la calidad de gestión de aprendizajes en docentes de las instituciones educativas secundarias urbanas San Juan Bautista 2023 - Tanchiva Pisco, Erika Gricel (2025)
This study examined the influence of the Pedagogical Management Committee's performance quality on teachers' learning management in Urban Secondary Educational Institutions of San Juan Bautista during 2023. The research, observational and prospective in nature, employed a causal correlational design with an explanatory approach. The population comprised 21 administrators and 252 teachers from urban secondary institutions in the district, utilizing a scaled questionnaire survey. The confirmatory factor analysis revealed KMO values of 0.94 and 0.93 for the studied variables, indicating significant correlations among items. The logistic regression, evaluated through Cox and Snell's pseudo R squared (0.059), Nagelkerke (0.072), and McFadden (0.035), demonstrated that the model explains between 3.5% and 7.2% of the variance in Teachers' Learning Management (TLM), showing a statistically significant yet limited fit. The findings confirmed that the Pedagogical Management Committee's quality significantly influences teachers' learning management, emphasizing the relevance of pedagogical leadership as a determining factor for continuous improvement in secondary education. The results suggest that optimizing the committee's performance could generate positive impacts on the educational community